A estrutura ontológica da linguagem e a queda no falatório em Ser e Tempo - Christiane Costa de Matos Fernandes (2016)
The present thesis focuses on demonstrating in what manner language (die Sprache) is the lattermost manifestation of the historicity of any meaning that can come to words as well as through what agency those meanings are upheld by a conjointly historical field of meaning, insofar as stated by Martin Heidegger in his work Being and Time (Sein und Zeit). As of this writing, our work aims at unraveling by what means language in its trivial use, or the talk (das Gerede), overshadows the historical aspect and the meanings that withstand the phenomenon of language. Hence, the present work is developed in two adjoining ways: the first one endeavors to describe the ontological structure of language deriving out of the resizing of Heidegger's question of being, that has the aim of indicating how the words, in context of enunciation, inherit their meaning from previous structures of the hermeneutic experience, that is, through the prior ontological understanding of the language. The second one aims at revealing the language phenomenon in the median everydayness as communication, or discourse (die Rede), which has already been expressed and is still expressed, always repeated and spread in the talk, that obliterates the comprehensive horizon by reducing all beings to an undifferentiated homogenization and making them available to our linguistic resources since it is the primary opening of the sense of being that any and all entities have.